Vitamin B12, Folic Acit and Ferritin Levels in Behcet's Patients - Etem, Arzu Akagac; Etem, Ebru Onalan; Turkmen, Sembol Yildirmak (Derman Medical Publ, 2014)
Aim: Behcet disease (BD) is a systemic disease presented with attacks and long-term course, involving many different organs and basic pathology of vasculitis. Many hypothesis was proposed the etiology of thrombosis and vasculitis in BD. One of those hypothesis its respect to originate from hyperhomocysteinemia. We aimed in this study to compare the level of vitamin B12, folic acit and ferritin in BD patients and healthy control groups. Material and Method: Seventy-three patients of BD diagnosed with criteria by the International Study Group and seventy-three healthy controls were retrospectively enrolled in this study. Subjects with above the upper reference limit vitamin B 12 concerned taking vitamin B 12 treatment were excluded. Levels of serum vitamin B12, folic acit and ferritin measured by competitive immunoassay and sandwich immunoassay respectively using direct chemiluminescent method on Advia Centaur XP (Siemens, USA) autoanalyzer with its commercial kits in both groups. Statistical analyze were performed with SPSS 11.5 programme. Results: The mean levels of vitamin B12, folic acid, and ferritin were not significantly different in patients with Behcet's disease when compared with the healthy controls (p=0.700, p=0.164, p=0.618, respectively). When the studied patients and controls were subdivided into subgroups according to sex vitamin B12, folic acid, and ferritin levels were not significantly different (female BD and control subgroups p=0,136, p=0,564, p=0,942 and male BD and control subgroups p=0,263, p=0,140, p=0,510respectively). Discussion: Vitamin B12, folic acid, and ferritin levels was not different between BD and healthy groups in our study. We are thinking that the subject sould be lighten with clinic studies -prospective, inquisitively elaborate and follow-up vitamin and other therapies-because of controversial reports in literature.
Keywords: Behcet Disease; Vitamin B12; Folic Acit; Ferritin